Advanced renal cell carcinoma: pathology and systemic therapy with a new role of zoledronic acid in management of skeletal metastases - Wcisło, Gabriel (Contemporary Oncology/Współczesna Onkologia, 2005)
Renal cell carcinoma (RCC) continues to represent a major therapeutic challenge. There is still observed the increased rate of incidence of RCC at the level of 2% per annum. Unfortunately, approximately 30% of patients develop distant metastases at first presentation. Progression of RCC accounts for additional 20% of cases with distant metastases to make up totally 50% of all RCC patients. The median survival of these patients is approximately 1 year, and the probability of survival at 2 years is 10% or even less. Metastatic RCC is extremly resistant to conventional chemotherapy. On the other hand, spontaneous regressions have been reported in some patients which suggests a role of immunity in fighting the malignancy. Thus, immunotherapy with infusions of interleukin-2 and interferon alfa have shown reproducible effects in patients with metastatic RCC. Some clinical trials have demonstrated the synergistic activity of the cytokines and anticancer agents (5-fluorouracil, vinblastine). The combination chemoimmunotherapy has revealed encouraging results of 15% to 45% response rate. Other studies have not confirmed the primary results. It has been estimated that bone metastases will develop in approximately 30% of patients with RCC. Bone metastases cause considerable skeletal morbidity, including bone pain, pathologic fractures, spinal cord compression, and hypercalcemia of malignancy. Bisphosphonates are the promising group of drugs with activity against activated osteoclasts which in turn lyse bone. Zoledronic acid provides clinical benefits for patients with bone metastases originating of RCC and other solid tumors. The drug delays the onset of skeletal-related events.